Pengaruh Iklan Blackpink Sebagai Brand Ambassador Terhadap Minat Beli dalam Platform Tokopedia - Tilman Eldon; Arvin Daffa Naufal; Misael Bistok Ricardo; Zulfan Zidni Ilhama; Enggal Aryadwika; Nur Aini Rakhmawati (International Forum of Researchers and Lecturers, 2024)
Technology in this modern era has an important role in the running of a business activity. One of the applications of technology that we often find is the use of advertisements with brand ambassadors to increase consumer interest in buying products. Tokopedia is one of the leading e-commerce companies in Indonesia that implements promotional strategies with advertisements using brand ambassadors to increase consumer buying interest on their platform. Blackpink, one of the biggest names in Korea, was appointed by Tokopedia to be one of their brand ambassadors in 2021. When these brand ambassadors succeed in attracting the attention of consumers, it will indirectly increase consumer buying interest. Therefore, the researcher intends to find the significance between Blackpink's role as a brand ambassador in Tokopedia advertisements and purchase intention on the Tokopedia platform. The data analysis method used is Simple Linear Regression using the SPSS version 25 program. Based on the results of data analysis, a correlation or relationship value (R) of 0.548 (54.8%) is obtained, this value indicates that the correlation or relationship between advertising and interest is a fairly strong relationship. The results of hypothesis testing and it is known that tcount > ttable, which is 2.761 > 1.987. Thus, Tokopedia advertisements featuring Blackpink as brand ambassadors significantly influence buying interest in the Tokopedia platform.